Mode II fracture characterization of wood using the Four-Point End-Notched Flexure (4ENF) test - de Moura, M. F. S. F. (2018)
This work addresses wood fracture characterization under mode II loading using the Four-Point End-Notched Flexure test. A suitable data reduction scheme based on specimen compliance, beam theory and equivalent crack model was developed with the aim of solving several disadvantages intrinsic to this fracture test. Following this methodology, crack length measurements in experimental tests required in classical procedures becomes unnecessary. Moreover, the execution of additional tests to measure the elastic properties are also unnecessary. The method was applied to experimental load-displacement curves to obtain the corresponding Resistance-curves. A ﬁnite element analysis including cohesive zone modelling was conducted to validate the followed procedure. It was veriﬁed that numerical load-displacement curve and Resistance-curve are well representative of the overall trends obtained experimentally. These results demonstrate good performance of the method, which makes the Four-Point End-Notched Flexure test a valuable and appealing alternative to conduct wood mode II fracture characterization.